2008
DOI: 10.1088/1478-3975/5/4/044002
|View full text |Cite
|
Sign up to set email alerts
|

Folate andS-adenosylmethionine modulate synaptic activity in cultured cortical neurons: acute differential impact on normal and apolipoprotein-deficient mice

Abstract: Folate deficiency is accompanied by a decline in the cognitive neurotransmitter acetylcholine and a decline in cognitive performance in mice lacking apolipoprotein E (ApoE-/- mice), a low-density lipoprotein that regulates aspects of lipid metabolism. One direct consequence of folate deficiency is a decline in S-adenosylmethionine (SAM). Since dietary SAM supplementation maintains acetylcholine levels and cognitive performance in the absence of folate, we examined herein the impact of folate and SAM on neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Data were captured at 3.125 kHz simultaneously accessing 16 channels and 12.5 kHz accessing 4 channels; the latter was used to validate the use of undersampling for the purpose of observing more channels. Prior studies using combinations of excitatory and inhibitory neuronal antagonists have confirmed synaptic origin of signals in these cultures (Serra et al, 2008a,b, 2010; Serra and Shea, 2009).…”
Section: Methodsmentioning
confidence: 71%
“…Data were captured at 3.125 kHz simultaneously accessing 16 channels and 12.5 kHz accessing 4 channels; the latter was used to validate the use of undersampling for the purpose of observing more channels. Prior studies using combinations of excitatory and inhibitory neuronal antagonists have confirmed synaptic origin of signals in these cultures (Serra et al, 2008a,b, 2010; Serra and Shea, 2009).…”
Section: Methodsmentioning
confidence: 71%
“…Choline- or choline-methionine-deficient diets induce severe depletion of hepatic folate in rats, suggesting that choline deficiency leads to increased utilization of folate to maintain hepatic methionine and S-adenosylmethionine [2830, 37]. Folate deficiency has recently been reported to reduce brain acetylcholine levels and cause abnormalities of synaptic function in vitro in mice that lack apolipoprotein E [33, 38]. The metabolic relationships among folate, choline, and acetylcholine have been increasingly recognized as important because of the roles of these compounds in brain plasticity and behavior [24, 21, 39, 40].…”
Section: Introductionmentioning
confidence: 99%
“…As described previously (17,2326), long-term (mature) cultures develop spontaneous signals that radiate across large areas of the culture, as evidenced by their simultaneous appearance at multiple electrodes. When recorded, spontaneous signals in our mature cultures exhibited a regular amplitude (40.0 5.0 V) and duration (0.8 0.2sec, mean standard deviation, n = 20 individual signals from 3 cultures from separate experiments).…”
Section: Resultsmentioning
confidence: 62%